New Difference Sequence Spaces Defined by Musielak-Orlicz Function - M. Mursaleen; Sunil K. Sharma; S. A. Mohiuddine; A. Kılıçman (Abstract and Applied Analysis)
We introduce new sequence spaces by using Musielak-Orlicz function and a generalized B∧ μ-difference operator on n-normed space. Some topological properties and inclusion relations are also examined.